Persistent organic pollutants in dusts that settled indoors in lower Manhattan after September 11, 2001 - Offenberg, John H; Eisenreich, Steven J; Gigliotti, Cari L; Chi Chen, Lung; Xiong, Judy Q; Quan, Chunli; Lou, Xiaopeng; Zhong, Mianhua; Gorczynski, John; Yiin, Lih-Ming; Illacqua, Vito; Lioy, Paul J (Journal of exposure analysis and environmental epidemiology, 2004)
The explosion and collapse of the World Trade Center (WTC) was a catastrophic event that produced an aerosol impacting many residents, workers, and commuters after September 11, 2001. In all, 12 bulk samples of the settled dust were collected at indoor locations surrounding the epicenter of the disaster, including one sample from a residence that had been cleansed and was once again occupied. Additionally, one sample was collected from just outside a fifth story window on the sill. These samples were analyzed for many components, including inorganic and organic constituents as well as morphology of the various particles. The results of the analyses for persistent organic pollutants on dusts that settled at indoor locations are described herein, including polycyclic aromatic hydrocarbons, polychlorinated biphenyls, and select organo-chlorine pesticides. The Σ 86 -PCB concentrations, comprising less than one part per million by mass of the bulk in the two samples analyzed, indicated that PCBs were of limited significance in the dust that settled at indoor locations across lower Manhattan. Likewise, organo-chlorine pesticides, Hexachlorobenzene, Heptachlor, 4,4′-DDE, 2,4′-DDT, 4,4′-DDT and Mirex were found at even lower concentrations in the bulk samples. Conversely, Σ 37 -PAHs comprised up to 0.04% (<0.005–0.036%) by mass of the bulk indoor dust in the 11 WTC impacted bulk indoor samples. Analysis of one sample of indoor dusts collected from a vacuum cleaner of a rehabilitated home shows markedly lower PAH concentrations (<0.0005 mass%), as well as differing relative contributions for individual compounds. In addition to similar concentrations, comparison of PAH concentration patterns (i.e. chemical fingerprints) shows that dusts that settled indoors are chemically similar to previously measured WTC dusts found at outdoor locations and that these PAH analyses may be used in identifying dusts of WTC origin at indoor locations, along with ascertaining further needs for cleaning.